Actividad antimicrobiana de hongos endofíticos aislados de Brugmansia suaveolens Bercht. & J. Presl (Research, Society and Development, 2021)
Natural products produced from endophyte fungi have a broad spectrum of biological activity and can be grouped into several categories. Antimicrobials constitute an important group of therapeutic agents, which can be produced and obtained from living organisms. The main objective of this study is to investigate the endophytic fungi and the leaves of Brugmansia suaveolens Bercht. & J. Presl as elicitors, aiming at the production of bioactive substances with antimicrobial properties. The extracts were prepared from 19 fungi isolated from the leaves of B. suaveolens Bercht. & J. Presl, used as a biotic elicitor. The extracts were obtained by fermentation in a submerged medium with the addition of leaves from its dry leaves, and the antimicrobial activity of its extracts was evaluated using the agar diffusion method. The results showed that 57% of the endophytic fungi showed antimicrobial activity after fermentation with the elicitor. It was observed that the antimicrobial activity was increased compared to control cultures. The leaves of B. suaveolens Bercht. & J. Presl presented bioactives that stimulated the production of a substance with antimicrobial activity by endophytic fungi, the study of such compounds showed promise to clarify the application potential of these bioactives.